Molecular effects of resistance elicitors from biological origin and their potential for crop protection - Wiesel, Lea; Newton, Adrian C.; Elliott, Ian; Booty, David; Gilroy, Eleanor M.; Birch, Paul R. J.; Hein, Ingo (Frontiers in Plant Science, 2014)
Plants contain a sophisticated innate immune network to prevent pathogenic microbes from gaining access to nutrients and from colonising internal structures. The first layer of inducible response is governed by the plant following the perception of microbe- or modified plant-derived molecules. As the perception of these molecules results in a plant response that can provide efficient resistance towards non-adapted pathogens they can also be described as ‘defence elicitors’. In compatible plant/microbe interactions, adapted microorganisms have means to avoid or disable this resistance response and promote virulence. However, this requires a detailed spatial and temporal response from the invading pathogens. In agricultural practice, treating plants with isolated defence elicitors in the absence of pathogens can promote plant resistance by uncoupling defence activation from the effects of pathogen virulence determinants. The plant responses to plant, bacterial, oomycete or fungal-derived elicitors are not, in all cases, universal and need elucidating prior to the application in agriculture. This review provides an overview of currently known elicitors of biological rather than synthetic origin and places their activity into a molecular context.